Sengketa Pembiyaan di Baitul Maal Wat Tamwil (BMT): (Studi Kasus Mekanisme Penyelesaian di Tingkat Internal) - Nugraha, Aldi; Fadhlan, Muhammad; Rafa, Mukhamad; Nurmaliah, Ima; Joni, Joni; Fauziah, Raihani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines how Baitul Maal wat Tamwil (BMT) resolves financing disputes internally. Employing a qualitative approach with library research, the study draws on scholarly articles, books, and related documents. Data were analyzed descriptively and qualitatively to identify common internal settlement practices that align with Sharia principles and national law. Results indicate that BMTs typically use deliberation among parties, mediation involving management or the Sharia Supervisory Board, and restructuring of financing as primary means to resolve conflicts. These options are favored to preserve institutional-member relationships and reduce adverse financial and social consequences. When internal measures do not succeed, disputes may be referred to Sharia arbitration or to religious courts. The findings highlight the importance of blending Sharia values with positive legal frameworks to ensure dispute resolution is fair, efficient, and sustainable.